Treasure Island / Robert Louis Stevenson - Alwin-Hill, Raymond; Stevenson, Robert Louis, 1850-1894. (New York : Waldman & Son, 1977)
The classic Robert Louis Stevenson story retold and adapted for the stage.
Faculty.
Keywords: Children's plays, American; Treasure Island (Imaginary place) -- Drama; Treasure troves -- Drama; Pirates -- Drama; Buried treasure -- Drama; Pirates -- Drama; Adventure and adventurers -- Drama; Plays